2020
DOI: 10.1002/bmc.4769
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and transcriptional changes in seminal plasma of asthenozoospermia patients

Abstract: This study was designed to investigate the metabolic and transcriptional alterations in seminal fluid caused by asthenozoospermia (AS). To address these issues, a method of metabonomics based on ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) and real‐time quantitative PCR (RT‐qPCR) was performed to identify some crucial biomarkers and transcription levels of the enzymes in seminal fluid. Seminal fluid samples were collected from 87 AS patients and 73 healthy males with normozoosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…On the other hand, we noted a significant decrease in six amino acids (glutamate, aspartate, methionine, tryptophan, proline, and alanine) in men with SOA compared to controls. Previous metabolomic studies have also reported a significant decrease in various amino acids, including the ones we identified, in the seminal plasma of men with male factor infertility 12,43 . Among these amino acids, glutamate is the most abundant in the seminal plasma, and its concentration is correlated with the sperm concentration, 31 whereas aspartate is correlated with the number and motility of the sperm 16 .…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…On the other hand, we noted a significant decrease in six amino acids (glutamate, aspartate, methionine, tryptophan, proline, and alanine) in men with SOA compared to controls. Previous metabolomic studies have also reported a significant decrease in various amino acids, including the ones we identified, in the seminal plasma of men with male factor infertility 12,43 . Among these amino acids, glutamate is the most abundant in the seminal plasma, and its concentration is correlated with the sperm concentration, 31 whereas aspartate is correlated with the number and motility of the sperm 16 .…”
Section: Discussionsupporting
confidence: 63%
“…Previous metabolomic studies have also reported a significant decrease in various amino acids, including the ones we identified, in the seminal plasma of men with male factor infertility. 12,43 Among these amino acids, glutamate is the most abundant in the seminal plasma, and its concentration is correlated with the sperm concentration, 31 whereas aspartate is correlated with the number and motility of the sperm. 16 Both these amino acids have been repeatedly shown to be decreased in men with male factor infertility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown the important roles of the metabolic pathways involving AAs in the regulation of parameters associated with semen quality (8)(9)(10). For example, metabolic disorders involving AAs are thought to be involved in the structural and functional alterations of spermatozoa in men with severe oligoasthenospermia (8).…”
mentioning
confidence: 99%